LEARNING ORIENTATION AND TRUST IN SMALL AND MEDIUM ENTERPRISE (SME) EXPORT COMPETITIVE ADVANTAGE - Md Daud Ismail (Asian Academy of Management Journal, 2013)
Trust in inter-organisational relationships is becoming an increasingly important topic in international business studies. Trusting relationships are even more important to small businesses with limited operational resources, which makes partnerships with foreign importers an important strategic consideration. When exporters pursue these endeavours, they are able to leverage partner company competencies. Organisations gain market knowledge and, thereafter, a greater export competitive advantage. This study examines the antecedents of relationships between small and medium export and import enterprises. This study also investigates the effects of Small and Medium Enterprise (SME) relationships on exporters’ competitive advantage. Based on a sample of 228 SMEs, trust positively and significantly affects competitive advantage. In addition, managerial commitment is crucial for SMEs pursuing trusting and beneficial relationships with foreign importers. We conclude this paper with a statement of limitations and recommendations for future research.